Symbiosis and pathogenicity of Geosmithia and Talaromyces spp. associated with the cypress bark beetles Phloeosinus spp. and their parasitoids. (2nd May 2022) - Meshram, Vineet; Sharma, Gunjan; Maymon, Marcel; Protasov, Alex; Mendel, Zvi; Freeman, Stanley
Summary: Fungi associated with cypress bark beetles are practically unknown in the Eastern Mediterranean. Our study focused on the fungi associated with the body parts and galleries of two indigenous cypress bark beetles, Phloeosinus armatus and P . bicolor, sampled from Cupressus sempervirens trees in different regions in Israel. Arbitrarily primed PCR, performed on genomic DNA of 302 isolates, clustered the fungal population into five distinct groups. Multilocus phylogeny, split‐network analyses and morphological characterization identified the isolates as Geosmithia omnicola, Geosmithia langdonii, Geosmithia sp. 708b, Geosmithia cupressina sp. nov. CBS147103 and Talaromyces cupressi sp. nov. CBS147104. Of these fungal isolates, G . cupressina and T . cupressi are newly described, and their morphological features and phylogenetic designations are presented. Inoculation of intact cypress saplings in an outdoor net‐house revealed that only the representative isolate T . cupressi sp. nov. CBS147104 causes 100% disease incidence, whereas Geosmithia spp. isolates are not pathogenic. A number of these fungi were isolated from parasitoids that emerged from branch and stem sections colonized by P . armatus . This study suggests a long and stable association between Phloeosinus and Geosmithia species, and a possible role for additional associated fungal species as pathogens or endophytes of C . sempervirens trees in Israel.